2014
DOI: 10.11564/28-3-615
|View full text |Cite
|
Sign up to set email alerts
|

Family planning counselling and use among clients seeking abortion services in private health facilities in Kenya

Abstract: Résumé Ce papier examine l'offre et l'utilisation des services de planification familiale chez les clients qui recherchent fréquentant les services d'avortement au niveau des établissements privés de santé privés au Kenya. Les données sont issues d'observations des interactions client-prestataires de services et des entretiens de sortie menées entre Mai -Juin 2013 auprès de 125 clientes provenant de 30 cliniques privées au niveau des zones de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…These findings imply that 60% of the women missed FP counselling when they visited the facility for any health reason; while 31.2% and 26.4% missed FP counselling at ANC and post-natal care (PNC) visits respectively. Similarly findings have been reported elsewhere [8,14,16,18,24]. Kanyangara et al reported a 6% missed opportunity of FP counselling in sub-Saharan country sites.…”
Section: Plos Onesupporting
confidence: 81%
See 1 more Smart Citation
“…These findings imply that 60% of the women missed FP counselling when they visited the facility for any health reason; while 31.2% and 26.4% missed FP counselling at ANC and post-natal care (PNC) visits respectively. Similarly findings have been reported elsewhere [8,14,16,18,24]. Kanyangara et al reported a 6% missed opportunity of FP counselling in sub-Saharan country sites.…”
Section: Plos Onesupporting
confidence: 81%
“…This creates an opportunity for FP information to be disseminated during pre-natal, post-natal, and maternal health service delivery. Provision of FP information and counseling is an essential aspect of Tanzania maternal health plan and provided free of charge [16][17][18]. During these visits women are expected to receive information on FP methods that are available, possible side effects, and the importance of resuming the FP after delivery [1].…”
Section: Introductionmentioning
confidence: 99%
“…Unplanned or unintended pregnancy poses a major economic, psychological, social, and religious challenge in women of reproductive age especially in developing countries (4). Despite the availability of a modern and effective contraceptive, it is one of the leading causes of maternal mortality and morbidity in developing countries due to unsafe and septic abortion practices (5). There is a strong correlation between abortion and contraception use, where as abortion incidence declines as contraceptive use increases in settings with steady fertility rates over time (6).…”
Section: Introductionmentioning
confidence: 99%